STUDY OF THE EFFECT OF WRAPPING APPLE VARIETIES WITH DIFFERENT PAPER BAGS ON THE CHEMICAL COMPOSITION DURING THE VEGETATION PERIOD (Web of Agriculture: Journal of Agriculture and Biological Sciences, 2025)
This study investigated the effect of wrapping apple fruits in different paper bags during the growing season on their chemical composition. The use of paper bags during fruit ripening affects their appearance, biochemical composition, and environmental safety. Using different paper materials (paraffined, mediated, natural), the content of antioxidants, the concentration of phenolic compounds, and the sugar content were analyzed. The results showed that the use of paper bags helps reduce pesticide residues on the skin of fruits and extend their shelf life. At the same time, changes in the balance of oxygen and carbon dioxide in the fruit were observed due to the effect of some paper bags on gas exchange. This study reveals the possibilities of effective use of paper bags in the production of environmentally friendly and safe fruits.